The information privileges of political elites in the conditions of social media development - E. I. Kutsaenko (Современная наука и инновации, 2024)
The article presents the results of a study of the influence of social media on the information privileges of political elites. In the ―Introduction‖ section, the author substantiates the relevance of the topic and problem of his research. In his opinion, it is determined by the rapid development of social media, which have become a tool of various political actors who use them to achieve various goals. With the development of social media, political elites face new difficulties in exercising information privileges, but at the same time receive new opportunities for information dominance. The study of the information privileges of political elites is becoming even more relevant in the context of an information war. In the section ―Materials and research methods‖ the author characterizes the empirical and methodological bases of his research. The first includes reports and reports from various research organizations, regulations, etc. The second includes the classical theory of elites, the modern theory of political communication and the modern theory of mediatization of politics. In the ―Literature Review,‖ the author systematizes publications related to the topic and problem of their research. He identifies three groups of works: 1) works that examine the interaction of elites with the mass media, their communication activity and strategies for mastering the information space; 2) works whose authors analyze the influence of social media on the political process; 3) works in which social media are correlated with such an important political science category as the political regime. In the ―Research results and their discussion‖ section, the author formulates a definition of information privileges, understanding them as priority access to the media space, which provides significant opportunities in the field of information dominance. He argues that, firstly, social media acts as a factor preventing political elites from exercising information privileges, because imply practices that contradict elite models of managing society, and secondly, that in order to realize information privileges and maintain their socio-political status in general, political elites are currently using two ―reactive‖ and one ―proactive‖ strategies. The author emphasizes that in conditions of political crises, through social media, the opposition is trying to eliminate the communication monopoly of political elites. The authors also point out that in the ―post-truth‖world, political elites receive new opportunities to exercise their information privileges. However, ―post-truth‖ circulating in the space of social media also determines the formation of opposition centers of information gravity. Using the latest data, he comes to the conclusion that the hybrid war unleashed against Russia involves the involvement of existing and the formation of new hostile centers of information gravity, the key task of which is precisely to undermine the information dominance of the Russian elite, and then to create and manage internal crises, in destabilizing the political regime in the country. In the ―Conclusion‖ section, the author summarizes his research, briefly listing the results obtained.